2020
DOI: 10.1186/s13018-020-02081-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of surgical procedures on thoracic myelopathy

Abstract: Purpose The surgical treatment of thoracic myelopathy is still controversial and also a challenge for spine surgeons. Therefore, the objective of this study was to review the related literature on the surgical treatment of thoracic myelopathy and try to define treatment guidelines for spine surgeons on thoracic myelopathy. Methods Relevant literatures were searched based on the PubMed, EMBASE, and Cochrane Library between January 2008 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…According to the Macnab efficacy evaluation, the excellent and good rate was 87.5%. Compared with traditional open surgery (34.6–76.7%) [ 8 ], this method may have obvious advantages. The above results serve as strong evidence of the clinical treatment effect of posterior full endoscopic surgery on TM secondary to OLF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Macnab efficacy evaluation, the excellent and good rate was 87.5%. Compared with traditional open surgery (34.6–76.7%) [ 8 ], this method may have obvious advantages. The above results serve as strong evidence of the clinical treatment effect of posterior full endoscopic surgery on TM secondary to OLF.…”
Section: Discussionmentioning
confidence: 99%
“…By removing the ossified ligamentum flavum and/or expanding the spinal canal to decompress the spinal cord, the nerve could be saved. Although the clinical effect of traditional treatments for thoracic ligamentum flavum ossification were clear, it still has many disadvantages, such as substantial trauma and a high rate of complications (34%~76.7%) [ 8 13 ], which often lead to additional pain and financial burden in patients and their families. In recent years, the endoscopic technique has been used for the treatment of ossification of the thoracic ligamentum flavum [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-surgical outcomes in DTM depend on many factors, such as the operative approach, causative pathology, symptom duration, and presence of additional stenosis. 30,104 For OLF, statistically significant improvements of JOA scores are reported, although recovery is typically incomplete. 57,59,112,113 Recovery is dependent on several factors, such as preoperative neurological status, duration of symptoms, imaging findings, age, sex, number of levels involved, and type of OLF.…”
Section: Presentation and Managementmentioning
confidence: 98%
“…In Japanese populations, in which most of the included studies were conducted, OLF and OPLL are the commonest causes, followed by disc herniation, with rare causes including calcification of the ligamentum flavum and degenerative spondylolisthesis. 11,[27][28][29][30][31] A recent systematic review found that in Japan, 45% of cases were OPLL, 36.4% OLF, 16.5% OPLL with OLF and 2.1% disc herniation, 31 whilst in China, 75.8% of cases were OLF, 13.8% disc herniation, 6.6% OPLL and 3.8% OPLL with OLF. 31 That same study found that in the US, disc herniation is the commonest aetiology with 95.7% of cases, with OLF making up 3.6% and OPLL .5%.…”
Section: Dtm Conditionsmentioning
confidence: 99%
“…Such a surgical procedure can directly remove the pressure substance in front of the spinal cord to achieve direct decompression. However, research has indicated that the incidence of complications in posterior circumferential decompression is much higher than that in single posterior decompression with more blood loss, although there are no signi cant differences in neurological recovery [15].…”
Section: Introductionmentioning
confidence: 98%